ANALISIS STRATEGI PENJUALAN WINGSFOOD DALAM MENINGKATKAN MINAT BELI KONSUMEN - Milawati Valantia; Syamsul Hidayat (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Instant noodles are an instant food product that is very popular with consumers around the world because of its practicality. Therefore, it is necessary for companies to analyze consumer behavior in order to understand their purchasing patterns. Based on data from Databoks, the Instant Noodle brand most frequently consumed by Indonesians is Indomie and Mie Sedaap is in second place. Of course, this is a reference so that the WingsFood company can provide above average customer satisfaction so that interest in repeat purchases increases. To find out strategies that can be used to increase purchases of Mie Sedaap, research was conducted on Strategy Analysis to Increase Consumer Purchase Interest in WingsFood Products Among Students. The method used is a survey method using a Likert scale. Data analysis uses validity tests, reliability tests, regression analysis, coefficient of determination and significance tests using a quantitative approach. The total sample was 121 respondents who came from students majoring in Regular Management 1, Bina Bangsa University. The results of this research conclude that brand image, product quality and price have an influence on purchasing decisions. In this research, the company PT. WingsFood is expected to be able to maintain and improve product quality and maintain prices in accordance with consumer purchasing power in order to increase customer satisfaction.